2011
DOI: 10.1007/s11605-011-1519-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Matrix Metalloproteinase-21 is Associated with Poor Overall Survival of Patients with Colorectal Cancer

Abstract: Our findings emphasize the important role of MMP-21 in the invasion and metastasis process in human colorectal cancer. It might also serve as a novel prognostic marker that is independent of, and additive to, the TNM staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
4
18
0
Order By: Relevance
“…Interestingly, compared with the cleavage peptide (LAQAVRSS), we found that the prodomain of MMP21 has a similar peptide sequence (LAQAVR) through the Swiss Prot database. Furthermore, MMP21 was recently shown to play an important role in tumor processing [14][15][16]26]. In our study, MMP21 was found to be upregulated in hepatocellular carcinoma and associated with microvascular invasion.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, compared with the cleavage peptide (LAQAVRSS), we found that the prodomain of MMP21 has a similar peptide sequence (LAQAVR) through the Swiss Prot database. Furthermore, MMP21 was recently shown to play an important role in tumor processing [14][15][16]26]. In our study, MMP21 was found to be upregulated in hepatocellular carcinoma and associated with microvascular invasion.…”
Section: Discussionsupporting
confidence: 59%
“…Current staging systems for CRC that are based on clinical and pathologic findings may have reached their limit of usefulness for predicting outcomes 23. Recent studies indicate that biomarkers are useful predicting factors, with some found to be even superior to AJCC stage 24–27. Thus, a substantial amount of research on CRC has focused on the discovery of specific biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In several human tumors, including colorectal cancer, breast cancer, prostate cancer, pancreatic cancer, Merkel cell carcinoma, hepatocellular carcinoma, up-regulated levels of MMP-21 have been found, generally in association with poor prognosis (Bister et al, 2007;Hegedüs et al, 2008;Huang et al, 2011;Suomela et al, 2009;Wu et al, 2011b).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%